Strengthening The Positioning of The Banking Industry in The People's Economy Bank in East Nusa Tenggara Province - Ni Putu Nursiani; I Komang Arthana; Viktorianus M. Da Lopes; Yonas Ferdinand Riwu (Dinasti Publisher, 2026)
Bank Perekonomian Rakyat (BPR) is a banking entity that plays an important role in strengthening the national economy, particularly by providing financing support to micro, small, and medium enterprises (MSMEs). BPR is expected to provide financial services to MSME entrepreneurs and rural communities who lack access to commercial banks. However, BPRs face a dilemma in carrying out their operations due to fundamental changes in the financial industry. Research conducted in NTT shows that BPRs compete with Commercial Banks, Cooperatives, Village-Owned Enterprises (BUMDes), and Financial Technology to maintain their financial sustainability. Competitive advantage can be achieved through optimal resource management, especially in the era of knowledge-based competition. This study aims to examine the positioning of BPR as the main pillar in supporting the growth of MSMEs and rural communities through inclusive and sustainable financial services. Positioning using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis is a way to understand the position of a company or product in the market by identifying internal and external factors that affect banking performance. The results of the research are expected to include BPR's strategic model in strengthening its position in the market and ensuring growth and financial sustainability in the midst of fierce competition, scientific articles in reputable journals, ISBN books, copyrights to the books, and news.